Students’ Perceptions towards the Use of VLE in a Fundamental English Course: A review of Smart Choice Online Practice and Smart Choice On the Move - Wongpornprateep, Pawarit; Boonmoh, Atipat (Journal of Studies in the English Language, 2019)
Computer assisted language learning (CALL) has been used as a teaching aid in language learning for the past several years. One of the examples of CALL integration in language teaching is the virtual learning environment (VLE). This study investigates Thai university students’ perceptions towards the use of VLE as a learning support in their fundamental English course. The websites discussed in this study served as complementary materials of the main textbook of the course, “Smart Choice” by Oxford University Press (2016) including its accompanying VLE materials “Smart Choice Online Practice” and “Smart Choice On the Move”. “Smart Choice Online Practice” was designed for use with personal computers, while “Smart Choice On the Move” was designed for use with smartphones. The data was obtained by implementing semi-structured interviews with 20 Thai university students taking a fundamental English course in academic year 2018. The interview data was transcribed and classified into themes. The findings detail the students’ perceptions regarding the noteworthy features of the VLE materials. In what follows we discuss the students’ viewpoints about the VLE materials as well as their pedagogical implications.